Surgical management of a foramen magnum tumor via a far-lateral approach using an oblique straight incision: a case series report and technique note - Bai, Jie; Jian, Zhi-heng; Chen, Peng; Cheng, Ye; Wang, Ya-ming; Chen, Gang; Xiao, Xin-ru (Frontiers in Oncology, 2024)
Objective To review our single-institution experience in the surgical management of foramen magnum tumors via a far-lateral approach using an oblique straight incision. Methods From October 2023 to January 2024, four cases of tumors in the foramen magnum area treated at the Capital Medical University-affiliated XuanWu hospital neurosurgery department were involved in this study. All cases were managed with a far-lateral approach using an oblique straight incision. We retrospectively reviewed the clinical and imaging data, as well as the surgical strategies employed. Results Three cases of foramen magnum meningiomas and one case of glioma of the ventral medulla. All cases underwent a far-lateral approach using an oblique straight incision; all cases had a gross total resection, and the wounds healed well without cerebral fluid leakage or scalp hydrops. Except for one case of right foramen magnum meningioma, which had dysphagia and pneumothorax, the other cases were without any postoperative complications. Conclusion A far-lateral approach using an oblique straight incision can preserve muscle integrity and minimize subcutaneous exposure, allowing for complete anatomical reduction of muscles. This craniectomy method is simple and replicable, making it worthy of further clinical practice.